Los Infiernos de El Escorial. Reflexiones acerca de las opiniones del P. Santos sobre el Panteón del Monasterio - Vega-loeches, José Luis (Anales de Historia del Arte, 2007)
The writings of the Hieronymite monk Fray Francisco de los Santos (c. 1616-1699), appear to be an inescapable source of understanding for the new conducted architectonic and pictorial interventions in the building throughout the 17th century. The great publishing success of the Descripción breve of the Monastery of S. Lorenzo, contains four Spanish editions and two translations in English; it shows the continuous interest and curiosity aroused by the monument of Felipe II. The Descripción breve is a likely first independent and exclusively artistic description of a Spanish historic building.